2020
DOI: 10.1016/j.ijheatmasstransfer.2019.119093
|View full text |Cite
|
Sign up to set email alerts
|

Heat flux distribution beneath evaporating hydrophilic and superhydrophobic droplets

Abstract: An experimental investigation of the heat and mass transfer to an evaporating hydrophilic water droplet using thin-foil thermography and droplet shape analysis is reported. These results have been compared with that of a superhydrophobic evaporating droplet. The hydrophilic droplet initially evaporated with a pinned contact line before unpinning and evaporating with a receding contact line. The largest heat flux is observed at the contact line region for both droplets. The hydrophilic droplet evaporated 34% fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Thus, the water resistance on the coverslips is weakened and the thermal resistance caused by the water decreases and accordingly an increase in heat transfer is expected. Gibbons et al (2020) examined the water droplet on the hydrophilic coated surface and the heat and mass transfer of the water droplet showing superhydrophobic properties and found that the evaporation rate of the water droplet on the hydrophilic coated surface was 34% faster [27].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the water resistance on the coverslips is weakened and the thermal resistance caused by the water decreases and accordingly an increase in heat transfer is expected. Gibbons et al (2020) examined the water droplet on the hydrophilic coated surface and the heat and mass transfer of the water droplet showing superhydrophobic properties and found that the evaporation rate of the water droplet on the hydrophilic coated surface was 34% faster [27].…”
Section: Resultsmentioning
confidence: 99%
“…Temperature measurement errors calibrated under ambient temperatures (5-25 • C) were about ±1 • C [21], which is inadequate to measure the interface temperature of the droplet. Gibbons et al [22] measured the temperature beneath the hydrophilic and superhydrophobic droplet with the IR thermography. However, the captured thermal image had relatively low spatial resolutions.…”
Section: Introductionmentioning
confidence: 99%
“…A traditional method of characterizing the contact angle of a solid-liquid interface is conducted using a side-view method, which is shown in Figure 1. In this configuration, an optical camera is placed parallel to the substrate being investigated [27][28][29][30]. The contact angle, in this approach, is determined by drawing a line from the contact line (solidliquid-gas interface) tangential to the liquid-gas interface.…”
Section: Introductionmentioning
confidence: 99%